Sensitivity of Cuscuta species and their hosts to Anethum graveolens essential oil - Sarić-Krsmanović, Marija M; Gajić Umiljendić, Jelena; Radivojević, Ljiljana; Šantrić, Ljiljana; Đorđević, Tijana; Đurović-Pejčev, Rada (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
The purpose of this study was to examine in vitro the herbicidal effect of an essentialoil of dill (Anethum graveolens) on germination and early seedling growth of two parasiticflowering plants in the genus Cuscuta (Cuscuta campestris and C. epithymum), as well as itsphytotoxic impact on germination and early seedling growth of two host plants (alfalfaand red clover). Chemical analysis of the essential oil extracted from dill leaves and flowersshowed that carvone (51.69%) and limonene (39.88%) predominated. The results of a seedbioassay showed inhibitory effects of different concentrations (1%, 0.5%, 0.1%, and 0.01% v v-1)of the essential oil of dill leaves on germination and early seedling growth of both testedspecies of the genus Cuscuta. Germination of C. campestris seeds was inhibited between 67%and 94%, while seed germination of C. epithymum was inhibited between 67% and 100%.A similar inhibitory effect was observed regarding the seedling length parameter. Moreover,the bioassay results indicated significant phytotoxic effects of dill essential oil on the seedgermination and early seedling growth of host plants. Red clover proved more sensitive aseven the lowest concentration inhibited germination by 35%, while higher concentrationscaused 70-100% inhibition. On the other hand, lower concentations inhibited germination ofalfalfa seeds by 5%, while higher concentrations caused greater inhibition (36-100%). Futureresearch should include both pot experiments and field micro-trials to determine herbicidal,i.e. phytotoxic, effects of dill essential oil on parasitic flowering plants and cultivated species.
Keywords: dodder; alfalfa; red clover; dill; essential oils; phytotoxicity; bioherbicide